PENGARUH KUALITAS PRODUK, HARGA DAN DAYA SAING PASAR TERHADAP VOLUME PENJUALAN USAHA KRIPIK SINGKONG “KURNIA” DI KABUPATEN LABUHANBATU - Sutriani sutriani; Zulkarnain Nasution; Meisa Nasution (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
This research is in the background by the declining sales volume of cassava crypt business marked by a decrease in crypt merchants. The problem in the study is whether there is an influence on product quality, price and market competitiveness simultaneously on the volume of cassava chips sales in Labuhanbatu. The sample used in this study was 100 respondents from the population of all cassava chips buyers in Labuhanbatu. This study uses multiple linear regression analysis. partially the quality of the product affected the sales volume of cassava chips, with a thitung value of 2,510 > t tables of 1,986, as well as the price affecting the sales volume on cassava chips with a t count value of 5,634 > t tables of 1,986 and market competitiveness affecting the sales volume in cassava chips with a tally value of -2,294 < t table 1,986. And simultaneously the quality of products, prices and market competitiveness have a significant effect on the sales volume of cassava chips. Based on the R value of the two variables X1, X2, X3 andY are 12.9% and the remaining 87.1% is influenced by other variables. Keywords: Product Quality, Price, Market Competitivenes,, Sales Volume